Gambar Sebagai Media Bimbingan Bermain dan Belajar Anak-Anak - Cucu Arumsari (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
The majority of drawing and drawing activities are liked by children because of the shape or color they like, but with increasing age and environmental influence not a few who are not interested in drawing or seeing pictures, because they are considered not useful or not too important compared to subjects in school. After a deeper study, it turns out that drawing and drawing save many benefits for the development of children. Among them can help motor development, the development of various intelligences and, no less important, can make children happy, especially if they can get support from the surrounding environment, it all contributes greatly to the success of children. in the future.